The GRK2 Promoter Is Regulated by Early‐Growth Response Transcription Factor EGR‐1. Issue 6 (9th July 2018) - Klenke, Stefanie; Engler, Andrea; Ecker, Daniel; Ochsenfarth, Crista; Danowski, Nina; Peters, Jürgen; Siffert, Winfried; Frey, Ulrich H.
Abstract: The G‐protein‐coupled receptor kinase 2 (GRK2) plays a major role in cardiovascular diseases, and its expression is increased in heart failure. However, only little is known about factors being involved in up‐regulation of GRK2 expression through transcriptional regulation of its promoter. Since the transcription factor early‐growth response 1 (EGR‐1) is also up‐regulated in patients with heart failure, we tested the hypothesis that EGR‐1 regulates GRK2 transcription. Stimulation of immortalized rat cardiomyocytes (H9c2) with phorbol 12‐myristate 13‐acetate (PMA) resulted in up‐regulation of Egr‐1 and subsequently of Grk2 mRNA expression, with maximum Grk2 expression ( p = 0.008) 5 hr after PMA stimulation and being abolished by actinomycin D, indicating a transcriptional mechanism. To identify naturally occurring variants affecting promoter transcriptional activity, we identified a novel G(‐43)A polymorphism (rs182084609), which surrounded a putative EGR‐1‐binding site. While the minor A allele frequency was rare (0.02), this variant was used to explore regulation by EGR‐1 and promoter construct with altered alleles at nt‐43 were subjected of reporter assays in human embryonic kidney cells (Hek293). Here, EGR‐1 over‐expression resulted in a more than twofold increase in GRK2 promoter activity but only in the presence of the G‐allele ( p = 0.04). In electrophoretic mobility shift assays, EGR‐1 over‐expression resulted in a specific binding of transcription factors only to the G oligonucleotide. Finally, EGR‐1 over‐expression resulted in increased GRK2 mRNA expression ( p = 0.03). We identified EGR‐1 as a regulator of GRK2 transcription. Suppression of GRK2 expression by inhibition of EGR‐1 binding to GRK2 might be a promising approach to mitigate adrenergic desensitization.